Conseguirá o Sr. Temer fazê-lo? - Terra, Fábio Henrique Bittes (Brazilian Keynesian Review, 2016)
This short paper analysis the pamphlet Uma ponte para o futuro, which presents the basic guidelines of Michel Temer’s government – by now, mid-2016, yet a temporary government. The analysis will be done divided in three sections. On the one hand, it will present the diagnosis how the pamphlet looks at the current economic problems in Brazil and the solutions proposed to resolve them. On the other hand, the paper realizes a Keynesian analysis over the document. Finally, as its concluding remarks, the paper debates the current political circumstances in Brazil as they are fundamental to define whether the Ponte para o futuro will be implemented or not.